Tests Result of the Prototype Monitoring System for the Operating Parameters of the Powered Roof Support in Real Conditions - Trzop, Konrad Łukasz; Szurgacz, Dawid (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Monitoring of operating parameters of machines and devices is recently used more often in hard coal mining. This solution is one of the elements of the intelligent mine concept. This concept means that the enterprise uses innovative technologies while considering economic and social factors. The aim of applying practical solutions under the guiding idea is to increase the efficiency of the production line and the safety of the crew`s work.
Keywords: geometry; pressure measurement; monitoring of powered roof support; work safety; work efficiency